Macrobotanical remains and preservational bias: an example from Moonggaroonggoo, Gooniyandi Country, Western Australia. Issue 2 (4th May 2019) - Dilkes-Hall, India Ella
Abstract: Archaeological excavation at Moonggaroonggoo, southern Kimberley, revealed preservation of macrobotanical remains in deposits dating to the late Holocene. Analysis of those remains shows limited species representation and biased preservation of plant remains, demonstrating that, with careful analysis, anthropogenic and non-anthropogenic remains can be differentiated. In this instance, deposition of macrobotanical material cannot be directly linked to cultural activities and instead the assemblage is best interpreted as one that reflects the local vegetation surrounding the cultural site.